THE INFLUENCE OF INTRINSIC MOTIVATION AND NON-PHYSICAL WORK ENVIRONMENT ON EMPLOYEE LOYALTY THROUGH WORK DISCIPLINE AT PT. CANNET ELEKTRIK INDONESIA - Padilla, Nurul; Hendra Galuh Febrianto (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
Intrinsic motivation, non-physical work environment and work discipline can affect employee loyalty. In this case, the lack of intrinsic motivation from within employees, as well as a non-physical work environment that has not been created properly and also the lack of employee work discipline are certainly factors causing the lack of employee loyalty. This study aims to determine the influence of intrinsic motivation and non- physical work environment on employee loyalty through work discipline at PT Cannet Elektrik Indonesia. This study uses quantitative research and survey research. The determination of the sample in this study uses the probability sampling technique with the saturated sample technique. The sample in this study was with 75 respondents of employees working at PT Cannet Elektrik Indonesia. The data obtained was analyzed using the PLS (Partial Least Square) shows that intrinsic motivation has a significant effect on employee loyalty. 2) The results of the analysis show that the non-physical work environment has a significant effect on employee loyalty 3) The results of the analysis show that work discipline has a significant effect on employee loyalty. 4) The results of the analysis show that intrinsic motivation has a significant effect on employee loyalty through work discipline. 5) The results of the analysis show that the non-physical work environment has a significant effect on employee loyalty through work discipline.